Ideação à inovação disruptiva: um estudo de caso sobre seus condicionantes - Cardoso, Marcos Milani (2013)
This present work represents a case study conducted with different business units and corporate areas in a Brazilian branch of a multinational company (acknowledged by its innovative strength in multiple sectors: auto parts, consumer goods and industrial goods), aiming to understand what inhibits or enables a more venturesome innovative approach towards more disruptive products (understood as those genuinely new, designed after actual demands and unmet needs, avoiding limitations of technological paradigms and the erroneous inertial persecution of the same competitive attributes). For doing so, the following main objectives are established: 1. Understand how selected determinants (environment, human resources, financial resources, processes, culture and strategy) impact the product innovation portfolio composition in the units selected; 2. Therefore, identify ideas sources that are most frequently used and those considered most effective in each unit studied. As the background for this analysis, the literature review outlined starts discussing some concepts (disruptive innovation and value co-creation particularly) which exhort to the importance of a broader innovative orientation, dribbling an inertial conservative behavior that seems quite deleterious. After that, an approach on the main drivers that mold the innovation orientation is outlined (covering the lockin risks and opportunities brought by open innovation amidst the innovation strategy perspectives). Finally, the bottlenecks in the idea generation phase (which has been reported by some recent studies as the major cause for an alleged gap in disruptive innovations) are explored, some multidisciplinary contributions on innovation applied creativity (ideation concepts from cognitive and social sciences) are brought and the most effective and commonly used sources of ideas according to recent researches are covered. The analysis identifies three main innovation orientations in the studied areas (tech drivers with offensive strategies; need seekers with opportunist strategies; and market readers with more dependent strategies), what seems to be determined by deliberate corporate definitions molded by a more conservative and centralizing cultural and strategic approach of the company, dedicating limited innovation scope and resources for the branch. The idea sources follows this three main innovation orientations, also being close to those traditionally used internationally: technologically oriented areas with more innovative capabilities (offensive innovation strategy) tend to find more efficient and popular the technological prospection sources; dependent innovation approaches tend to rely on a more basic usage of voice of customer sources; and the opportunist orientation is the only approach more focused on open innovation methods (which generally have limited adoption). Besides and in general, internal and voice of customer sources tend to be disseminated and effectively used independently of the orientation.